Penerapan Model Problem Based Learning Melalui Metode Picture And Picture Untuk Meningkatkan Hasil Belajar Kelas VI SDN 01 Pasar Ladang Panjang - Hamidah, Nur (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This research aims to improve the learning outcomes of Pancasila among students of Islamic Religious Education (PAI) through the implementation of the Project-Based Learning (PBL) method. The study was conducted in two cycles, with the first cycle using conventional methods and the second cycle using PBL. The results show that the implementation of PBL significantly improved students’ learning outcomes in cognitive, affective, and psychomotor aspects. Students became more active in discussions, more critical in analyzing the material, and more capable of linking theory to real-life situations. Therefore, PBL is proven to be an effective method for teaching Pancasila, enhancing students’ understanding, skills, and attitudes toward the material taught.